1998
DOI: 10.1007/s004360050415
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of BALB/c mice to nymphs and larvae of Ixodes ricinus after modulation of IgE production with anti-interleukin-4 or anti-interferon-γ monoclonal antibodies

Abstract: BALB/c mice infested three times with nymphs or larvae of Ixodes ricinus ticks do not acquire resistance as assessed by evaluation of both tick attachment and the weight of engorged nymphs or larvae. Tick challenge causes a gradual increase in total IgE antibody production from the first to the third infestation. Anti-tick IgG antibodies are never detected. When the mice are treated with anti-interleukin-4 (anti-IL-4) or anti-interferon-gamma (anti-IFN-gamma) monoclonal antibodies (mAbs) 1 day before each infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 24 publications
2
22
1
Order By: Relevance
“…It is anyway in keeping with the acquired resistance in multi-infested rabbits never observed in mice [35].…”
Section: Discussionmentioning
confidence: 94%
“…It is anyway in keeping with the acquired resistance in multi-infested rabbits never observed in mice [35].…”
Section: Discussionmentioning
confidence: 94%
“…During this time, hosts acquire resistance or develop tolerance to the ectoparasites. In contrast to resistant hosts, for example rabbits infested with I.ricinus adults (Bowessidjaou et al 1977), no difference was observed in the percentage of attachment or the weight of engorged larvae or nymphs of I. ricinus during reinfestations of BALB/c mice (Christe et al 1998). In order to feed as well as to transmit pathogens successfully ticks must maintain blood flow and control the immune response of their host.…”
Section: Discussionmentioning
confidence: 99%
“…BALB/c mice tolerated frequent feedings by pathogen-free larval or nymphal I. ricinus. The two instars seem to engorge more effectively on repeatedly exposed mice (Christe et al 1998). In nature, I. ricinus larvae and nymphs feed abundantly on yellow-necked mice (Apodemus flavicollis) and black-striped mice (Apodemus agrarius).…”
Section: Discussionmentioning
confidence: 99%
“…Total IgE antibody levels were measured by enzyme-linked immunosorbent assay (ELISA) using two kinds of rat anti-mouse IgE monoclonal antibody (mAb) as previously described (Christe et al 1998). Three wells were done in replicate for each analysis.…”
Section: Measurement Of Total Ige Antibodiesmentioning
confidence: 99%
“…However, the host developed cutaneous immediate and slight delayed-type hypersensitivities. BALB/c mice infested with I. ricinus nymphs or larvae develop a Th2 polarization of the immune response (Ganapamo et al 1995;Christe et al 1998). In the present study we subjected BALB/c (H-2d), C57BL/6 (H-2b), and C3H (H-2k) mice to 3 successive infestations with 15 nymphs of I. ricinus to study the in¯uence of the genetic background on the acquisition of resistance against ticks and on the production of total IgE.…”
Section: Introductionmentioning
confidence: 99%